Interactions between sleep disruption, motor learning, and p70 S6 kinase 1 signaling. Issue 3 (14th October 2019) - Kam, Korey; Kang, Mihwa; Eren, C Yasemin; Pettibone, Ward D; Bowling, Heather; Taveras, Shantal; Ly, Annie; Chen, Rebecca K; Berryman, Natasha V; Klann, Eric; Varga, Andrew W
Abstract: Offline gains in motor performance after initial motor learning likely depend on sleep, but the molecular mechanisms by which this occurs are understudied. Regulation of mRNA translation via p70 S6 kinase 1 (S6K1) signaling represents one potential mechanism, as protein synthesis is thought to be increased during sleep compared to wake and is necessary for several forms of long-term memory. Using phosphorylation of ribosomal protein S6 (RpS6) as a readout of S6K1 activity, we demonstrate that a period of 10 h of acute sleep disruption impairs both S6K1 signaling and offline gains in motor performance on the rotarod in adult wild type C57/Bl6 mice. Rotarod motor learning results in increased abundance of RpS6 in the striatum, and inhibition of S6K1 either indirectly with rapamycin or directly with PF-4708671 diminished the offline improvement in motor performance without affecting the initial acquisition of rotarod motor learning when sleep is normal. In sum, S6K1 activity is required for sleep-dependent offline gains in motor performance and is inhibited following acute sleep disruption, while motor learning increases the abundance of striatal RpS6. Thus, S6K1 signaling represents a plausible mechanism mediating the beneficial effects of sleep on motor performance.